The Languages of COVID-19 Translational and Multilingual Perspectives on Global Healthcare - Wilson, Steven; Blumczynski, Piotr (2022)
This collection advocates languages-based, translational research to be part of the partnerships and collaborations required to make sense of, and respond to, COVID-19 as one of the major global challenges of our time.　Bringing together scholars and practitioners from a wide range of disciplines, this volume is bound by a common thread stressing the importance of linguistic sensitivity, (inter)cultural knowledge and translational mediation in the frontline response to COVID-19. Featuring contributors from around the world and reflecting on the language used to frame COVID-19 in diverse cultural contexts of the Global North and Global South, the book proposes that paying attention to the transmission of ideas, ideologies, narratives and history through processes of translation results in a broadening of social, cultural and medical understandings of COVID-19. Spanning nearly 20 signed and spoken languages, the volume argues that only in going beyond an Anglophone perspective can we better understand the cultural, social and political facets of the pandemic and, in turn, produce a comprehensive, efficient global response to disease management.　This book will be of interest to scholars in translation and interpreting studies, modern languages, applied linguistics, cultural studies, Deaf Studies, intercultural communication and medical humanities.